Quantification of Swertiamarin from Whole Plant Powder of Swertia densiflora (Griscb.) Kashyap. Collected in Different Seasons - SHAILAJAN, SUNITA; ABHISHEK, J.S. (Asian Journal of Chemistry, 2010)
In this paper, the comparative quantification of Swertiamarin from Swertia densiflora (Griscb.) Kashyap in different periods, in order to identify the best period for harvest is investigated. The plant powder was first extracted with methanol and then in chloroform. The final residue was reconstituted in methanol and used for quantitation. Chromatography was performed on silica gel 60 F254 HPTLC plate, with ethyl acetate:methanol:water, 7.5:1.5:1.2 (v/v), as mobile phase. Quantitation was achieved by densitometric scanning at 244 nm (λmax) in reflectanceabsorbance mode. The response to swertiamarin was linear function of concentration over the range 30 to 100 μL mL-1 in the extract of Swertia densiflora (Griscb.) Kashyap. The amount of swertiamarin in Swertia densiflora (Griscb.) Kashyap. whole plant powder was found to be 2.94 mg g-1 in the month of March, 1.59 mg g-1 in October and 1.18 mg g-1 in December.